Konsep Manusia Menurut Dayak Wehea Kalimantan Timur Dalam Terang Filsafat Martin Buber - Yovinus Andinata (Universitas Katolik Parahyangan, 2023)
The focus of this research is to explore the concept of man according to Dayak Wehea in the light of Martin Buber's philosophy. Thus, the data mining and research site are centered on the Wehea Dayak Tribe. This research departs from the author's awareness of the noble cultural values ​​contained in customs, which in the course of time began to be eroded by the currents of time. In the midst of this modern era, the values ​​of local wisdom are starting to be neglected and many local people do not understand the values ​​and meaning behind these customs and culture. Departing from this phenomenon, this research attempts to explore and document local wisdom values ​​specifically regarding the concept of humans as relational creatures as promoted by Martin Buber. The methodology used in this research is a qualitative method through literature study by processing existing data. Apart from that, to ensure the authenticity of the writing regarding the customs of the Wehea Dayak Tribe, interviews were also conducted with resource persons who are traditional leaders who understand and still implement these customs. From the research results, it was found that the concept of humans as relational creatures as promoted by Martin Buber is actually pervasive and manifested in the life and culture of the Wehea Dayak Tribe, specifically this conception is manifested in traditional birth, marriage and death ceremonies.